Pengaruh Metode Teams Games Tournament Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Akidah Akhlak Kelas VIII MTS Sa Al-Falah Sumberasri Tahun Pelajaran 2023/2024 - Afrida Nur Laili; Faza Faizatul Wahidah (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This research is motivated by several problem factors that occur in classroom learning, one of which is the lack of references and teacher innovation in the use of learning methods, and it turns out that there are still students who ignore learning about faith and morals which are considered less interesting in delivering the material, the aim is to determine the influence of the Teams Games Tournament method on Student Learning Outcomes in the Faith and Morals Subject of Class VIII MTs Sa Al-Falah in the 2023/2024 Academic Year. This research uses a type of quantitative research with a Pre-Experimental Design approach in the form of a One Group Pretsest-Posttest Design pattern. The population in this research uses class VIII, totaling 25 students as the Pre-test and Posttest Class. The sampling technique used by researchers is Saturated Sampling. Where all members of class VIII students were used as samples. The class was tested using 25 questions to determine whether it was valid and reliable. Data analysis in the research is the pre-requisite test which includes the Normality Test and Homogeneity Test, and the T Test using the Paired Sample Test. The research results obtained were the results of studying the Moral Aqidah subject using the Teams Games Tournament method using the Paired Sample Test with the help of the SPSS version 22 program, obtained a t_count value of 4.880 with a t_table value of 2.063. With this value, it can be seen that the t_count > t_table value (4.880 > 2.063), so it can be concluded that H0 is rejected and Ha is accepted. Judging from the second decision, the significance value can be seen from the Sig (2-tailed) result of 0.000. This shows that the significance level of 0.05 is greater than the Sig value. (2-tailed) or (0.000 < 0.05), then it can be concluded that H0 is rejected and Ha is accepted. So it can be concluded that there is an influence of the Teams Games Tournament method on student learning outcomes.